Log*4*(x+5)=log*4*(2x-7)

Simple and best practice solution for Log*4*(x+5)=log*4*(2x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Log*4*(x+5)=log*4*(2x-7) equation:


Simplifying
Log * 4(x + 5) = log * 4(2x + -7)

Reorder the terms:
goL * 4(5 + x) = log * 4(2x + -7)

Reorder the terms for easier multiplication:
4goL(5 + x) = log * 4(2x + -7)
(5 * 4goL + x * 4goL) = log * 4(2x + -7)
(20goL + 4goxL) = log * 4(2x + -7)

Reorder the terms:
20goL + 4goxL = glo * 4(-7 + 2x)

Reorder the terms for easier multiplication:
20goL + 4goxL = 4glo(-7 + 2x)
20goL + 4goxL = (-7 * 4glo + 2x * 4glo)
20goL + 4goxL = (-28glo + 8glox)

Solving
20goL + 4goxL = -28glo + 8glox

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '28glo' to each side of the equation.
20goL + 28glo + 4goxL = -28glo + 28glo + 8glox

Reorder the terms:
28glo + 20goL + 4goxL = -28glo + 28glo + 8glox

Combine like terms: -28glo + 28glo = 0
28glo + 20goL + 4goxL = 0 + 8glox
28glo + 20goL + 4goxL = 8glox

Add '-8glox' to each side of the equation.
28glo + 20goL + -8glox + 4goxL = 8glox + -8glox

Reorder the terms:
28glo + -8glox + 20goL + 4goxL = 8glox + -8glox

Combine like terms: 8glox + -8glox = 0
28glo + -8glox + 20goL + 4goxL = 0

Factor out the Greatest Common Factor (GCF), '4go'.
4go(7l + -2lx + 5L + xL) = 0

Ignore the factor 4.

Subproblem 1

Set the factor 'go' equal to zero and attempt to solve: Simplifying go = 0 Solving go = 0 Move all terms containing g to the left, all other terms to the right. Simplifying go = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(7l + -2lx + 5L + xL)' equal to zero and attempt to solve: Simplifying 7l + -2lx + 5L + xL = 0 Reorder the terms: 5L + 7l + -2lx + xL = 0 Solving 5L + 7l + -2lx + xL = 0 Move all terms containing g to the left, all other terms to the right. Add '-5L' to each side of the equation. 5L + 7l + -2lx + -5L + xL = 0 + -5L Reorder the terms: 5L + -5L + 7l + -2lx + xL = 0 + -5L Combine like terms: 5L + -5L = 0 0 + 7l + -2lx + xL = 0 + -5L 7l + -2lx + xL = 0 + -5L Remove the zero: 7l + -2lx + xL = -5L Add '-7l' to each side of the equation. 7l + -2lx + -7l + xL = -5L + -7l Reorder the terms: 7l + -7l + -2lx + xL = -5L + -7l Combine like terms: 7l + -7l = 0 0 + -2lx + xL = -5L + -7l -2lx + xL = -5L + -7l Add '2lx' to each side of the equation. -2lx + 2lx + xL = -5L + -7l + 2lx Combine like terms: -2lx + 2lx = 0 0 + xL = -5L + -7l + 2lx xL = -5L + -7l + 2lx Add '-1xL' to each side of the equation. xL + -1xL = -5L + -7l + 2lx + -1xL Combine like terms: xL + -1xL = 0 0 = -5L + -7l + 2lx + -1xL Simplifying 0 = -5L + -7l + 2lx + -1xL The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| r+20=16 | | cos(39)=x/2 | | 11/v=8/5 | | -2(3S-5)-10=-3(9S+3)-4 | | y=5x^2-45x+100 | | 3w^2-2w+2=0 | | 8x+28-8x=28 | | 42=2/3x | | 7x-1=9x-15 | | X/12-46=6 | | -6u+46=6u | | x-(0.2x)=0.6 | | 5/3u=25 | | -(5X+4)-(-4X-9)=13 | | 12y^2+23y+5= | | 9v^2-30+25=0 | | 4+9k=-5 | | 6w-2=2w+58 | | 9v^2-30v-25=0 | | 8x=16/7 | | D=26/pi | | http://media1.acellus.com/Library/00001022_223_A1.gif | | 56+8m=128 | | 4y^2+17y-15= | | 14y+1=1y+27 | | n-17=-13 | | 17n-70=168 | | 8x-10=8x-6 | | 42=4x+2x | | 4a+1=1a+25 | | f(x)=0.15x+5 | | 8y-5y=27 |

Equations solver categories